Boldness in Male and Female Zebrafish (Danio rerio) Is Dependent on Strain and Test - Mustafa, Arshi; Roman, Erika; Winberg, Svante (Frontiers in Behavioral Neuroscience, 2019)
Differences in selection pressure in nature and labs have profound effects on zebrafish strains. The wild zebrafish is found mainly in northern parts of India. The widely used AB strain of zebrafish has been domesticated over several decades. Recently, there has been an upsurge in availability of genetically modified lines, e.g. the speigeldanio (spd), which has a mutation in the fibroblast growth factor receptor 1a (fgfr1a) gene. Our knowledge on behavioral differences between different zebrafish strains, relative to wild-caught zebrafish is limited. In the present study we compare boldness of offspring (F1) of wild-caught fish, AB and fgfr1a -/- zebrafish. In addition, we compared boldness of males and females of these strains. A second aim of the study was to compare the behavior of fish from these strains when tested in different behavioral assays, i.e. shelter seeking, novel tank diving and scototaxis tests. The results demonstrate that behavioral variation exists both within and between the strains, but interpretation of boldness reveals a complex pattern in which behavior depend on an interaction between sex, strain and test. Therefore, a careful assessment of various strains of fish using both males and females is warranted in order to strengthen interpretation of results. This is especially important in studies where zebrafish are used as model organisms for human conditions as well as studies evaluating effects of pharmacological substances on behavior.